POAC Learning Management in the Pancasila Student Profile Strengthening Project: A Case Study at State Elementary School 01 Sedayu - Azizah, Alfiana; Nisa, Choirun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study analyzes POAC learning management (planning, organizing, im-plementing, and controlling/evaluating) in implementing the Pancasila student profile strengthening project at SD Negeri 01 Sedayu. Method: This study employs a case study methodology and a descriptive qualitative technique. The data in this study consisted of primary data, namely, class II teachers and principals, additional data sources from other teachers, and documentation. Methodology: The methodology used in the research of Joyful Learning method in junior high school is semi-structured interviews and school observation, which are used to collect data using a qualitative research approach. Results: Learning management in the implementation of P5 at SD Negeri 01 Sedayu includes: (1) Planning: The school held a meeting, formed a team of facilita-tors, assessed school readiness, selected project dimensions and themes, de-termined time allocations and project modules, and used an independent teaching platform in P5 planning. (2) Organizing: A facilitator team with a structure that includes principals, teachers, and extracurricular coaches with their respective roles and responsibilities. (3) Implementation: Teachers choose themes and activities that suit the needs of students through the stages of introduction, contextualization, action, and documentation of project re-sults. (4) Evaluation: Evaluation is done through direct observation, non-test methods, formative and summative assessment, and constructive feedback. Applications/Originality/Value: The novelty of this research lies in the in-depth exploration of the role of implementing learning management with the POAC approach in implement-ing P5 with a sustainable lifestyle dimension in elementary schools. The findings indicate that the successful execution of the project to improve Pan-casila's student profile is influenced by management.